ASUPAN PROTEIN NABATI DAN KEJADIAN ANEMIA WANITA USIA SUBUR VEGAN - Nugroho, Fajar Ari; Handayani, Dian; Apriani, Yosi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThe purpose of this study was to determined the role of vegetable protein intake and anaemia incidence among vegan reproductive aged women. This study was observational research with cross-sectional study design. Sixty-five subjects were selected by simple random sampling method. Data collection for intake was done by 24-hours recall technique, and haemoglobin levels was measured by cyanmethemogloblin method. The results showed that 26.1% from 31-anaemia vegan subjects classified as less vegetable protein intake individuals, and 43% from 34-non anaemia vegan subjects known as enough vegetable protein intake individuals. Chi-square test authenticate that there was a significant relationship between the vegetable protein intakes with anaemia incidence among vegan reproductive aged women (p=0.002). The conclusion showed that vegetable protein intake has a role to the risk of anaemia incidence among vegan reproductive aged women.Keywords: anaemia, reproductive aged women, vegan, vegetable proteinABSTRAKTujuan penelitian ini adalah mengetahui peran asupan protein nabati terhadap kejadian anemia pada wanita usia subur (WUS) vegan. Penelitian yang dilakukan adalah penelitian observasional dengan desain cross sectional. Sebanyak 65 subjek WUS dipilih menggunakan metode simple random sampling. Pengambilan data asupan dilakukan menggunakan metode 24-hours recall, sedangkan kadar hemoglobin dianalisis menggunakan metode cyanmethemoglobin. Hasil penelitian menunjukkan 31 WUS vegan yang anemia sebesar 26,1% diantaranya menunjukkan memiliki asupan protein kurang, sedangkan 34 WUS vegan yang tidak anemia (43%), memiliki asupan protein nabati cukup. Analisis chi square menunjukkan bahwa terdapat hubungan yang signifikan antara asupan protein nabati dengan kejadian anemia (p=0,002). Kesimpulan penelitian ini adalah asupan protein nabati berperan terhadap risiko anemia pada WUS vegan.Kata kunci: anemia, protein nabati, vegan, WUS